2014
DOI: 10.1177/1088767914536985
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Homicide and Assault Across Large U.S. Cities

Abstract: Although most crimes follow seasonal cycles, homicide is an apparent exception. The absence of homicide seasonality is surprising given that assault, a closely related offense, has an obvious annual pattern. Focusing on large U.S. cities, this article reevaluates seasonality in homicide rates using data with more extensive spatial and areal dimensions than in previous research. Panel decompositions reveal seasonal cycles in both homicide and assault rates. Seasonality stands out more clearly in assault, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…Mares () found strong positive relationships between crime and expected monthly temperatures. This is further confirmed by direct examination of seasonality, such as in recent studies by Carbone‐Lopez and Lauritsen () and McDowall and Curtis (). Put simply, crime has a strong seasonality that needs to be properly accounted for in any examination of the relationship between weather and crime.…”
Section: Introductionsupporting
confidence: 80%
“…Mares () found strong positive relationships between crime and expected monthly temperatures. This is further confirmed by direct examination of seasonality, such as in recent studies by Carbone‐Lopez and Lauritsen () and McDowall and Curtis (). Put simply, crime has a strong seasonality that needs to be properly accounted for in any examination of the relationship between weather and crime.…”
Section: Introductionsupporting
confidence: 80%
“…Evidence arguing against this approach though is the fact that assaults and homicides may differ in general trends (McDowall & Curtis, 2015). It is also the case that homicides are often examined because they are viewed as more reliable measures of violent crime due to differential reporting (Loftin & McDowall, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although the model can undoubtedly be improved, we take this as a simplified baseline model, not unlike fixed effects models used in prior research (McDowall & Curtis, 2015; McDowall & Loftin, 2009). The random effects model has the added benefit over the fixed effects model of shrinking future predictions.…”
Section: Time Series Fan Charts For Within-city Comparisonsmentioning
confidence: 99%
“…While some reported increased homicide rates during summer months (e.g., Ceccato, 2005;McDowall et al, 2012), others have not found support for a seasonal pattern (e.g., Abel, Strasburger, & Zeidenberg, 1985;Yan, 2000). McDowall and Curtis (2015) also identified a December spike in homicides that nearly reached the July peak.…”
Section: Temporal and Temperature Variations Of Violent Crimementioning
confidence: 99%